Diversity and distribution patterns of soil macroarthropod communities in the Nianchu River Basin, Tibet, China - Wang, Zhuang-Zhuang; Zhang, Peng; He, Kai; Zhu, Shi-Ying; Pu, Bu (Frontiers in Ecology and Evolution, 2024)
The study of how soil fauna interact with soil ecosystems is an important research field. At present, there has been little research on the diversity and distribution patterns of soil macroarthropods and on the relationship between soil fauna and environmental factors in Tibet. In total, 2880 soil macroarthropods were captured from 19 plots in the Nianchu River Basin, and the soil macroarthropod Hill numbers was at its lowest in spring. Sea buckthorn forest habitats had the highest Hill numbers. We found that Carabidae, Lycosidae, and Formicidae were always dominant species during seasonal changes in the Nianchu River Basin. Among the four different habitat types studied, Carabidae always appeared across the four studied habitat types and was one of the most significant taxa. The niche range of soil macroarthropods was wetland habitat > farmland habitat > sea buckthorn forest habitat > grassland habitat, and their community within sea buckthorn forest habitats was stable. The niche breadth of soil macroarthropods was the largest in summer, and the community was stable. Soil temperature and soil water content were the most important factors affecting the alpha diversity of soil macroarthropods, while altitude and soil temperature were the most important factors affecting their beta diversity. In summary, the results provide a comprehensive overview of the seasonal and habitat dynamics of soil macroarthropods in the Nianchu River Basin; it is strongly believed that the research carried out in this paper can contribute valuable information toward further research on the soil fauna diversity and ecological functions in this area and provide a strong scientific basis for the protection and sustainable development of the Nianchu River Basin ecosystem.